2011
DOI: 10.1063/1.3526956
|View full text |Cite
|
Sign up to set email alerts
|

Explicit correlation and intermolecular interactions: Investigating carbon dioxide complexes with the CCSD(T)-F12 method

Abstract: We have optimized the lowest energy structures and calculated interaction energies for the CO(2)-Ar, CO(2)-N(2), CO(2)-CO, CO(2)-H(2)O, and CO(2)-NH(3) dimers with the recently developed explicitly correlated coupled cluster singles doubles and perturbative triples [CCSD(T)]-F12 methods and the associated VXZ-F12 (where X = D,T,Q) basis sets. For a given cardinal number, we find that results obtained with the CCSD(T)-F12 methods are much closer to the CCSD(T) complete basis set limit than the conventional CCSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 65 publications
(91 reference statements)
6
43
0
Order By: Relevance
“…6,7 Shortly after the gas phase studies, a number of theoretical ab initio calculations appeared which predicted the existence of two T-shaped isomers, a C-bound (the most stable isomer) and an O-bound (a higher energy structure). [8][9][10][11] As shown below, our new infrared spectra confirm the existence and stability of the T-shaped O-bonded CO 2 -CO in a helium buffer. Additionally, we measure two of the four intermolecular frequencies of this isomer.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…6,7 Shortly after the gas phase studies, a number of theoretical ab initio calculations appeared which predicted the existence of two T-shaped isomers, a C-bound (the most stable isomer) and an O-bound (a higher energy structure). [8][9][10][11] As shown below, our new infrared spectra confirm the existence and stability of the T-shaped O-bonded CO 2 -CO in a helium buffer. Additionally, we measure two of the four intermolecular frequencies of this isomer.…”
supporting
confidence: 49%
“…10 However, a more recent and higher level ab initio calculation 11 gives a corrected binding energy of 409 cm −1 for isomer 1. Anyway, it seems clear from theory that isomer 1 (C-bonded) is considerably more strongly bound than isomer 2 (O-bonded).…”
mentioning
confidence: 99%
“…Numerous quantum-chemical studies of the systems' intermolecular potential energy surface (IPES) have been reported. [3][4][5][6][7][8][9][10][11][12][13] High level of electron correlation, extensive basis sets, and inclusion of basis set superposition errors prove mandatory as the IPES is extremely flat near the global potential energy minimum. A recent comprehensive work reports a complete 5D ab initio IPES composed of 23 000 high level single-point energies in configuration space and settles that the global potential energy minimum has a planar and T-shaped geometry of C 2v symmetry with the oxygen atom of H 2 O bound to the C atom and the H atoms pointing away from the CO 2 molecule 14 ( Fig.…”
mentioning
confidence: 99%
“…The C-C distance of 3.23Å from the PES is 0.01Å larger than the minimum distance taken from the best literature calculation 22 ; both are lower than the experimental distance of 3.277Å 21 , mainly as a result of non-rigidity of the intermolecular bond. A direct calculation of the interaction energy for this geometry gives −1.859 × 10 −3 E h , which is within 0.01 × 10 −3 E h of the best calculated value 22 . The difference of ∼ 0.03 × 10 −3 E h between the PES and calculation is similar to the RMSE of 0.024 × 10 −3 E h reported in section III.…”
Section: Fig 4 Comparison Of Calculated Interaction Energies (Symbomentioning
confidence: 83%